2018
DOI: 10.3389/fphys.2018.01268
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Retinal Architecture in Diabetic Retinopathy: Disruption of Ocular Physiology and Visual Functions by Inflammatory Gene Products and Pyroptosis

Abstract: Diabetic patients suffer from a host of physiological abnormalities beyond just those of glucose metabolism. These abnormalities often lead to systemic inflammation via modulation of several inflammation-related genes, their respective gene products, homocysteine metabolism, and pyroptosis. The very nature of this homeostatic disruption re-sets the overall physiology of diabetics via upregulation of immune responses, enhanced retinal neovascularization, upregulation of epigenetic events, and disturbances in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 195 publications
(206 reference statements)
1
43
0
1
Order By: Relevance
“…The key events of DR are angiogenesis and easy hemorrhage into the pre-retinal space or the vitreous cavity, resulting in severe loss of vision [27]. The present results confirmed the occurrence of hemorrhage in the retina of diabetic rats, and EOFAZ ameliorated edema and hemorrhage in OPL and GCL.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The key events of DR are angiogenesis and easy hemorrhage into the pre-retinal space or the vitreous cavity, resulting in severe loss of vision [27]. The present results confirmed the occurrence of hemorrhage in the retina of diabetic rats, and EOFAZ ameliorated edema and hemorrhage in OPL and GCL.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, novel therapeutic methods and targets in the prevention and treatment of DR must be developed. Considerable effort has been dedicated to developing new drugs for DR. One of the promising ones is an agonist of peroxisome proliferator activated receptors (PPARs) [27]. In our previous study, we found that EOFAZ activates PPAR-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy is considered to be the complication of diabetes of most concern that has affected over one‐third of the total diabetic population. [ 34 ] Besides hyperglycaemia, oxidative stress and chronic low level inflammation have been reported to be implicated in development and progression of DR. [ 7,35,36 ] Currently, usage of natural (plant‐based) therapeutics has gained significance owing to their lesser toxicity and no side effects. Previous studies have pointed out that RN, a polyphenol flavonoid possesses various pharmacological activities including anti‐allergic, anti‐diabetic activities and anti‐angiogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Despite glycemic control being the initial treatment for DR as the severity of the condition is initially a function of the degree of HG, glucose management tends to be ineffective in the later stages as chronic HG eventually produces irreversible damage. 2,11 The mainstay treatment for PDR and DME is anti-VEGF antibody injections into the vitreous chamber. Granted the antibodies are more effective than traditional laser retinal ablation therapy, the antibodies have their fair share of downfalls including a hefty price tag, a short half-life entailing frequent injections and consequential poor patient compliance.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The early stage of the disease is termed Non-Proliferative Diabetic Retinopathy (NPDR), characterized by the presence of intra-retinal hemorrhages, microaneurysms, and cotton wool spots from infarcted nerve tissue. 2,3 NPDR has the potential to advance to a more severe stage of the disease called Proliferative Diabetic Retinopathy (PDR) which is distinguished by the presence of pathological retinal neovascularization. 4 The novel vessels often lack the conventional integrity and if left untreated, may lead to hemorrhages within the vitreous and precipitate tractional retinal detachment.…”
Section: Introductionmentioning
confidence: 99%